Efficacy and Safety of Rimegepant for the Acute Treatment of Migraine: Evidence From Randomized Controlled Trials - Gao, Bixi; Yang, Yanbo; Wang, Zilan; Sun, Yue; Chen, Zhouqing; Zhu, Yun; Wang, Zhong (Frontiers in Pharmacology, 2020)
Background As one of the novel therapeutic drugs that targets Calcitonin gene-related peptide (CGRP), 75 mg rimegepant has been used for the acute management for migraine, which is one of the most common neurological diseases worldwide. Several clinical trials have been conducted to investigate the efficacy and safety of rimegepant for the acute management of migraine, but no systematic review of existing literature has been performed. Hence, we performed a meta-analysis to investigate the efficacy and safety of rimegepant in treatment of patients with migraine. Method Pubmed, Embased, and Cochrane Library were searched from January 2001 to August 2019 for randomized controlled trials (RCTs). Four RCTs with 3827 patients were finally included in our study. Result We pooled 3827 patients from 4 RCTs, the primary endpoints were freedom from pain or most bothersome symptom and pain relief at 2 hr postdose. We found that 75 mg rimegepant led to a significant freedom from pain (P < 0.001), pain relief (P < 0.001), and freedom of most bothersome symptom (P < 0.001) at 2 hr postdose compared with placebo. In addition, there is no statistically significant increase in adverse events compared with placebo. Conclusions 75 mg rimegepant has good efficacy and safety for acute treatment of migraine. Further studies are needed to compare the efficacy of rimegepant with traditional drugs for acute management of migraine.